Mapping of Diarrhea among Under-Five Children Based on Household Basic Sanitation in Pagurawan Health Center, Batu Bara Regency - Winni R.E. Tumanggor; Indra Chahaya (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Diarrhea in under-five children continued to be the leading cause of morbidity in Batu Bara District. This research investigated the relationship between basic sanitation and diarrhea among under-five children and its spatial distribution in the Pagurawan Health, Batu Bara Regency. The research employed a cross-sectional observational analytical design. The population was all mothers who have under-five children as many as 2310 population then determining the sample size using the Lemeshow formula with a total of 105. The samples were taken by purposive sampling selected by proportional from 9 rural. Data analysis used the is-square test for bivariate analysis and the overlay technique for spatial analysis. The technique performed for spatial is the overlay technique. The research revealed a relationship between the incidence of diarrhea in under-five children and water supply (p=0.034), while latrines (p=0.191), waste management (p=1.000), and wastewater disposal (p=0.825) were not. Spatial results found that the highest cases of diarrhea were in Pematang Nibung Village with a vulnerability status. Based on this research, water supply is related to the incidence of diarrhea among under-five children. Meanwhile, the latrines, waste management, and wastewater disposal are not related to the incidence of diarrhea among under-five children in the Pagurawan Community Health Center with a vulnerability status in Pematang Nibung Village. Keywords: Diarrhea, Sanitation, Under-five children